Defensin pattern in chronic gastritis: HBD-2 is differentially expressed with respect to Helicobacter pylori status. Issue 5 (1st May 2003) - Wehkamp, J; Schmidt, K; Herrlinger, K R; Baxmann, S; Behling, S; Wohlschläger, C; Feller, A C; Stange, E F; Fellermann, K
Abstract : Background/Aims: Recent reports have suggested that Helicobacter pylori infection induces the mucosal antibiotic peptide human β defensin 2 (HBD-2). Therefore, the present study investigated mRNA and peptide expression of four different defensins in the upper gastrointestinal tract in patients with H pylori positive and negative chronic gastritis. Materials/Methods: Biopsies from the oesophagus to the duodenum were taken during routine gastroscopy in 71 individuals. Total RNA was extracted and the reverse transcription polymerase chain reaction was performed with primers for human defensins 5 and 6 (HD-5/6) or HBD-1 and HBD-2. Paraffin wax embedded tissue from gastric resections was tested for HD-5, HBD-1, and HBD-2 by immunohistochemistry. Results: Helicobacter pylori colonisation was associated with an increased percentage of positive biopsies with respect to HBD-2 in the corpus (p < 0.05). Helicobacter pylori had no impact on the gastric expression of HD-5 and HBD-1, whereas HD-6 was increased in the fundus. The abundant expression of α defensins in the duodenum and β defensins in the oesophagus served as a positive control in each individual. Immunohistochemical analysis confirmed the presence of the HD-5, HBD-1, and HBD-2 peptides in gastric resection specimens. Conclusions: The recently described induction of HBD-2 upon H pylori infection was confirmed in a clinical setting of chronic gastritis. This phenomenon may be mediated by components of the pathogen itself or may occur secondary to immune events in chronic inflammation.